24.7k views
4 votes
X=2Y=56x + 10y + y - x²

1 Answer

2 votes

Answer: 63

Given that x = 2 and y = 5

Below is the expression given


\begin{gathered} 6x+10y+y-x^2 \\ \text{Substitute the value of x and y into the expression} \\ 6(2)+10(5)+5-(2)^2 \\ =\text{ 12 + 50 + 5 - 4} \\ =\text{ 62 + }5\text{ - 4} \\ =\text{ 67 - 4} \\ =\text{ 63} \end{gathered}

The answer is 63

User Rias
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.